VIABILITAS BENIH KAYU KUKU (Pericopsis mooniana THW) TERHADAP UMUR TAHUN PENYIMPANAN DAN TAKARAN GIBERELIN - Mazhfia Umar; Rahmah Dzulhajjah; Ikraeni Safitri (Politeknik Pertanian Negeri Samarinda, 2023)
This study aims to determine the viability of Kayu Kuku seeds which are influenced by the treatment of seed storage age and gibberellin hormone. This research was conducted at the Plastic House of the Arbuscular Mycorrhizal Association, Southeast Sulawesi Branch. Using the Completely Randomized Design (CRD) factorial method and repeated 3 times so that it requires 900 seeds in amount. The results showed that the interaction of treatment with storage age 0 years and without gibberellins had the highest average value on the variable percentage of germination (96%), germination (93%), the average seed germination per day (MDG) (3,20), and the interaction of 1 year seed storage age and 150 ppm gibberellin concentration gave the highest value to the variable time to germination (MGT) of 6.60. Therefore, nail wood seeds need to be germinated directly without going through annual storage and without giving gibberellins concentration.